RAILWAY SLEEPERS - Suyunov Dilshod Tursunbayevich; Ne'matov Firdavs Dilshodovich (Bright Mind Publishing, 2026)
This scientific article presents a DSc-level systematic analysis of railway sleepers as fundamental components of railway track superstructure. The study investigates structural characteristics, load distribution mechanisms, and operational performance of sleepers under static and dynamic loading conditions. Mechanical properties of timber, concrete, and composite sleepers are comparatively evaluated, including their interaction with ballast and long-term deformation behavior. Quantitative assessment of stress distribution under increasing axle loads and high-speed conditions is performed to develop a scientifically grounded approach for service life prediction and reconstruction planning. The results provide theoretical and practical recommendations aimed at improving reliability, safety, and economic efficiency of railway infrastructure.
Keywords: Railway sleepers, concrete sleepers, timber sleepers, ballast interaction, dynamic load, track superstructure, deformation, modernization.